Evaluating the Use of QRIS in MSME Services: Insights for Financial Education in Tawang, Tasikmalaya - Hartono, Muhammad Fauzan; Ramadhani, Dimas Bagus; Rosalia, Indah; Nandang, Nandang (Journal Corner of Education, Linguistics, and Literature, 2024)
This study examines the use of Quick Response Code Indonesian Standard (QRIS) in Micro, Small, and Medium Enterprises (MSMEs) in Tawang District, Tasikmalaya, focusing on its impact on transaction efficiency and service quality. QRIS, a digital payment system introduced by Bank Indonesia, enables cashless, contactless payments through smartphones, thus offering a solution to slow cash transactions and improving operational efficiency. The research aims to explore how QRIS adoption enhances MSME competitiveness by increasing market reach, reducing operational costs, and improving customer service, particularly in post-pandemic Indonesia. Data collected through interviews, observations, and documentation from MSME owners in the district reveal that businesses such as Rumah Papi Bakery, Warteg Kahrisma Bahari, Bosqu Barber, and Azka Laundry have benefited from QRIS in terms of transaction speed, customer satisfaction, and financial management. The study also addresses the challenges of QRIS adoption, such as the need for a stable internet connection and public understanding of the system.